Diagnosis of learning styles in agricultural technology transfer scenarios in Colombia - Ospina Parra, Carlos Eduardo; Garcia Marquez, Andrea; Romero Rubio, Laura Cristina; Florez Tuta, Natalia (Journal of Learning Styles, 2022)
One of the problems of rural development and technical change in the agricultural sector is the low appropriation of technology by producers, technical assistants and extension workers, this, among other factors, is influenced by the strategies and methodologies used in transfer processes technology and learning. AGROSAVIA developed the methodology to identify the learning styles (EdA) of the participants in technology transfer activities in the Colombian agricultural sector (MIDEAS), consisting of four motivational, social, perceptual and strategic dimensions. The objective of the research is to identify the predominant learning styles of agricultural producers, technical assistants and researchers and their relationship with some demographic factors. The instrument was applied to 726 people, the data were processed in a multiple correspondence analysis (ACR) and simple frequency tables. In all three groups, preferences such as motivation to apply the acquired knowledge, work in large groups, auditory and written perceptual channels, and information processing through practical and reflective activities prevail. There is a reflective tendency for women and an auditory trend for men. They are inputs that serve to develop better strategies for linking agricultural technology for the adoption and appropriation of technologies.
Keywords: Adoption; Technical Assistant.; Ttechnical Change; Farmer